NILAI TUKAR RUPIAH MELEMAH - Ferinton Mahmud (JURNAL LENTERA AKUNTANSI, 2016)
ABSTRACT Foreign exchange (FX) in banking industry and financial market, an activity of exchanging two or more currencies, has been done since 2000 years ago. It was written in the Bible that outside the temple, money lending and money changing activities between Israeli currency-Shakel and Roman currency-Dinari was done based on  foreign exchange conversion rate.After FX crash in Europe (1944), United States and England sought the solution by implementing Free, Stable and Multilateral Monetary System using Gold Standards’ Concept or known as Bretton Woods Agreement. It was along with the founding of International Monetary Funds which serves to stabilize and monitor currency exchange using “All Currency to USD or Gold”. Recently, the FX trading activities significantly affect the economy of a country including Indonesia. The depreciation of IDR against USD to IDR 13,393 gave impacts to President Jokowi government and perceived as more burden. The perception is normal since the IDR value is considered much weaker when compared to IDR 12,600/USD during the situation of global economic crisis in 2008. Certainly there is strong expectation that the depreciation of IDR against USD is only temporary, and consequently the demand for USD will soon back to normal. To realize this expectation, it needs synergy from all stakeholders involved such as government, OJK and BI, so that it will give positive impact to the foreign exchange market.Keyword: Foreign exchange, banking, rupiah